Actual and estimated adenoma detection rates: a 2‐year monocentric colonoscopic screening outcome in Shenzhen, China. Issue 4 (16th March 2020) - Zeng, Li; Chua, Eng G.; Xiong, Ying; Ding, Shihua; Ai, Hui; Hou, Zhibo; Loke, Mun F.; Goh, Khean L.; Tay, Chin Y.; Marshall, Barry J.; Zhu, Fuqiang; Sun, Dayong
Abstract: Background and Aim: While adenoma detection rate (ADR) is an important quality metric for screening colonoscopy, it remains difficult to be accessed due to the lack of integrated endoscopy and pathology databases. Hence, the use of an adenoma‐to‐polyp detection rate quotient and polyp detection rate (PDR) has been proposed to predict ADR. This study aimed to examine the usefulness of estimated ADR across different colonic segments in two age groups for Shenzhen people in China. Methods: We retrospectively analyzed 7329 colonoscopy procedures performed by 12 endoscopists between January 2012 and February 2014. The PDR, actual ADR, and estimated ADR of the entire, proximal, and distal colon, and within each colonic segment, in two patient age groups: <50 and ≥50 years, were calculated for each endoscopist. Results: The overall polyp and adenoma prevalence rates were 19.1 and 9.3%, respectively. The average age of adenoma‐positive patients was significantly higher than that of adenoma‐negative patients (54 ± 12.6 years vs 42.9 ± 13.2 years, respectively). A total of 1739 polyps were removed, among which 826 were adenomas. More adenomatous polyps were found in the proximal colon (60.4%, 341/565) than in the distal colon (40.9%, 472/1154). Overall, both actual and estimated ADR correlated strongly at the entire colon level and within most colonic segments, except for the cecum and rectum. In both age groups, these parameters correlated strongly within the traverse colon and descending colon. Conclusion: Caution should be exercised when predicting ADR within the sigmoid colon and rectum. Abstract : This aim of this retrospective study was to examine the correlations between the actual and estimated adenoma detection rate (ADR) across different colonic segments in two age groups for Shenzhen people in China. The overall polyp and adenoma prevalence were 19.1% and 9.3%, respectively. While the actual and estimated ADR values correlated strongly within the traverse colon and descending colon in both age groups, caution should be exercised when predicting ADR within the sigmoid colon and rectum.